1994
DOI: 10.1111/j.1600-0773.1994.tb01096.x
|View full text |Cite
|
Sign up to set email alerts
|

Should Probenecid be Used to Reduce the Dicloxacillin Dosage in Orthopaedic Infections? A Study of the Dicloxacillin‐Saving Effect of Probenecid

Abstract: Reduction in the dosage of dicloxacillin from 500 mg to 250 mg 3 times a day would mean lowering of costs and less side-effects in orthopaedic infections. In this cross-over study, the serum concentrations of dicloxacillin were measured in 9 patients after administration of dicloxacillin 500 mg 3 times a day (dicloxacillin 500 mg) and after co-administration of 250 mg dicloxacillin and 250 mg probenecid 3 times per day (dicloxacillin 250 mg+probenecid 250 mg). Concentrations were measured every hour after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Probenecid is an anion channel blocker (1) and uricosuric agent originally developed to slow the rate of excretion of penicillin (2). It is now in use in combination with a number of other antibiotics and pharmacological agents to reduce their required dosages (3)(4)(5). In several types of cells, probenecid has been used to prevent the leakage of the calcium indicator, fura-2, since this leakage reduces the accuracy of measurements of intracellular calcium concentration ([Ca2+]j) (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probenecid is an anion channel blocker (1) and uricosuric agent originally developed to slow the rate of excretion of penicillin (2). It is now in use in combination with a number of other antibiotics and pharmacological agents to reduce their required dosages (3)(4)(5). In several types of cells, probenecid has been used to prevent the leakage of the calcium indicator, fura-2, since this leakage reduces the accuracy of measurements of intracellular calcium concentration ([Ca2+]j) (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Since probenecid is a frequently administered drug (2)(3)(4)(5), and there is some confusion in the literature concerning its mode of action, we have investigated its effects on the responses of platelets to several aggregating and release-inducing agents, including the thrombin receptor-activating peptide SFLLRN, also known as TRAP. In addition, we have explored the combined inhibitory effects of probenecid and penicillin G.…”
Section: Introductionmentioning
confidence: 99%
“…It inhibits renal tubular urate resorption and has been found to decrease the levels of excretion of several medications, probably through inhibition of organic ion transporter 1 in renal tubular cells. Several studies have been published indicating that probenecid given one to three times daily at doses ranging from 250 to 1,000 mg can result in significant increases in the plasma concentrations of other approved medications (7,15,17,22,23). Probenecid demonstrates dose-dependent pharmacokinetics and nonlinear elimination (10,35).…”
mentioning
confidence: 99%
“…This means that dicloxacillin has the same volume of distributions in the different organs as was used above for inulin. Dicloxacillin is cleared primarily by the kidney in these subjects [12] and there is a large component of renal tubular secretion that is blocked by probenecid [18] determined by the parameter Tclr [kidney]. (Other studies have indicated that the liver can account for 40% or more of the total clearance [16].…”
Section: Resultsmentioning
confidence: 99%